The role of the 13C isotope of the Tree Ring in Recording of Carbon Cycle Change in Atmosphere - E. Ristin Pujiindiyati (Jurnal ILMU DASAR, 2014)
Some natural materials such as tree rings, rocks, sediments, ice cores, coral reefs, shell fish and micro fossil record the chemical, physical and biological changes in atmosphere that had taken place in the past. One of these changes which are recorded in tree rings is C-13 isotope. Through the measurement of ratio of 13C compared to 12C (defined as 13C value), it can be known atmospheric CO2 conditions in the past to reflect the present conditions. Present value of 13C in atmospheric CO2 is -7.5 ‰ that had decreased gradually from -6.69 in 1956. Pre-industrial 13C value in atmospheric CO2 is not available. However, the historical records of those are stored in tree rings. Starting from pre-industrial era about 1850 up to 2000, the records of 13C value in some tree rings which are spread in northern hemisphere showed decreasing value ranging from 0.60/00 to 2.30/00. Major factors contributing to variability of these 13C values are pollution effects and climatic effects. Besides those, some effects such as choice of the wood components, inner ring variability and juvenile stage of trees are also correlated to variability of 13C value. Records of 13C value from tree rings defined that atmospheric CO2 from pre-industrial era were between 240 ppm and 310 ppm then this concentration continuously increase to 340 ppm at present. Integrated biospheric carbon flux calculated for 13C records in tree rings using four models from the year of 1850 to 1975 showed an increasing value between 135 Gt and 345 Gt. Keywords : Tree rings, C-13 isotope, atmospheric CO2